The miracle season [videorecording (DVD)] - Hunt, Helen, 1963-; Moriarty, Erin; Yarosh, Danika, 1998-; Hurt, William (20th Century Fox Home Entertainment, 2018)
After the tragic death of star volleyball player Caroline "Line" Found, a team of dispirited high school girls must band together under the guidance of their tough-love coach in hopes of winning the state championship.